EKSISTENSI PARIWISATA SONGA ADVENTURE DAN PERUBAHAN SOSIAL MASYARAKAT CONDONG KABUPATEN PROBOLINGGO - Rizky, Vresty Meyditiya; Suhartini, Elly (Jurnal ENTITAS SOSIOLOGI, 2013)
Following the problem formulation in this research "How was the Existence of “Songa Adventure” Tourism Place and Social Change of Condong Society Probolinggo Regency?”, the purpose of this research was to describe the existence of Songa Adventure tourism and social change of Condong community Probolinggo Regency. In this research, the researcher used descriptive qualitative research method, and the informants were determined by purposive sampling technique. Data collection was by observation, interview, and documentation. Meanwhile, the examination of data validity was done by member check (informant cross-check). The existence of Songa tourism has brought changes to the villagers of Condong. The business opportunities in their environment led to social change in the fields of economy, education and social behavior that occurred in Condong village community members. The existence of Songa Adventure tourism either directly or indirectly also provided significant effects on the process of education in human resource development in Condong village. Keywords: the existence of tourism, social change of society